Persepsi Tokoh Agama Pondok Pesantren Hidayatullah Balikpapan Tentang Anak Sah Menurut Pasal 99 Ayat 1 KHI - Hidayati Hidayati; Abdurrohim Abdurrohim (Ulumul Syar'i : Jurnal Ilmu-Ilmu Hukum dan Syariah, 2022)
This research is motivated by differences in the perception of religious leaders of the Hidayatullah Islamic boarding school in Balikpapan in responding to the provisions of legal children as regulated in Article 99 paragraph 1 of the KHI, considering whether or not a child is legal is a very important matter. The purpose of this study was to determine the perception of the religious leaders of the Hidayatullah Islamic Boarding School about the legitimate children contained in the article as well as a review of Islamic law. This type of research is a descriptive field research. In collecting data, the researcher used interview techniques with informants, namely religious leaders who were at the Hidayatullah Islamic boarding school in Balikpapan, then the data was analyzed by data reduction, data display, and data verification. In the article it seems as if it gives legal tolerance to children born in legal marriages, even though the distance between marriage and the birth of children does not reach the minimum age limit of the womb, so that while the baby in the womb is born when the mother is in a marriage that is legal child, then the child can be called a legitimate child as well. In conclusion, in Islam a legitimate child is a child born as a result of a relationship between a man and a woman in a legal marriage, a child can be assigned to his father at least 6 months after the marriage, this is not regulated in positive Indonesian law.